Penicillin to prevent recurrent leg cellulitis: a critical appraisal. (December 2014) - van Zuuren, E.J.; Fedorowicz, Z.; Alper, B.; Mitsuma, S.F.
Summary Aim Thomas et al. compared the effectiveness of prophylactic low‐dose penicillin vs. placebo in patients with recurrent cellulitis for preventing the disease. Setting and design Participants of this double‐blind randomized controlled trial were recruited at 28 hospitals in the U.K. and Ireland between July 2006 and January 2010. Study exposure Patients with two or more episodes of cellulitis of the leg were randomized to receive low‐dose oral penicillin (250 mg twice daily) or placebo over 12 months with a follow‐up period of up to 3 years. Outcomes The primary outcome was the time to a first recurrence. Secondary outcome measures were the proportion of participants with a repeat episode of cellulitis during the prophylaxis phase and during the follow‐up phase, the number of repeat episodes of cellulitis, the proportion of participants with new oedema or ulceration during the prophylaxis phase and during the follow‐up phase, the number of nights in hospital for cellulitis, the number of adverse drug reactions or adverse events of interest (death, nausea, diarrhoea, thrush, rash, severe skin reactions, sepsis and renal failure), cost–effectiveness and predictors of response. Results Of the 533 patients screened, 274 were eligible and included in the trial (136 were assigned to the penicillin group and 138 to the placebo group). The median time to a first recurrence of cellulitis was 626 days in the penicillin group and 532 days in the placebo group. During the 12 months of treatment 30 (22%) of 136 patients in the penicillin group had a recurrence compared with 51 (37%) in the placebo group [hazard ratio 0·55, 95% confidence interval (CI) 0·35–0·86, P = 0·01; number needed to treat 7, 95% CI 4–9]. After the 12‐month treatment period, during the follow‐up there was no difference in the rate of first recurrence (27% in both groups). There were fewer repeat episodes in the penicillin group than in the placebo group during the treatment period (76 vs. 122, P = 0·03) and no difference during subsequent follow‐up (43 vs. 42). There was no statistically significant difference between the groups in the number of participants with an adverse event (37 in the penicillin group vs. 48 in the placebo group, P = 0·50). Conclusions Thomas et al. concluded that low‐dose penicillin was effective in preventing recurrent cellulitis in people with recurrent disease during prophylactic treatment, but that the effect reduced progressively after the discontinuation of penicillin.